Associations of exposure to polycyclic aromatic hydrocarbons with hearing in U.S. Adults - Xiuju Li; Zhaofeng Liu; Xiaohong Ding; Yuanling Zhou; Tingting Yu; Jin Jiang (Scientific Reports)
Abstract Polycyclic aromatic hydrocarbons (PAHs) pollution and hearing loss are important issues in the environment and public health. However, current research still lacks data on their association in real-world environments. This study included 658 American adults who participated in the National Health and Nutrition Examination Survey (NHANES) from 2015 to 2016. The correlation between single PAH exposure and hearing was estimated by the weighted logistic regression, the overall association between mixed PAHs and hearing was evaluated by Bayesian kernel machine regression and grouped weighted quantile sum regression, and the important chemicals were identified in this study. The results showed that the 1-Hydroxynaphthalene (1-OHNa) was positively correlated with the hearing condition, hearing level and hearing threshold (OR = 1.41, 95% CI 1.08–1.84, P < 0.01; OR = 1.41, 95% CI 1.04–1.87, P < 0.05; OR = 4.34, 95% CI 1.74–10.81, P < 0.01, respectively). And 1-Hydroxypyrene (1-OHP) was positively correlated with the hearing condition and hearing threshold (OR = 1.83, 95% CI 0.99–3.36, P < 0.05; OR = 5.83, 95% CI 1.31–26.03, P < 0.05, respectively) after using covariate correction. The results of BKMR and WQS indicated a positive correlation between overall PAHs exposure and decreased hearing, and the higher the overall exposure to PAHs, the greater the risk of hearing loss. Further analysis revealed that 1-OHP was an important chemical substance related to PAHs and hearing. This result was consistent with the results of the single PAH exposure model. These insights provide a critical new perspective on the association between PAHs and hearing, highlighting the urgent need for strategies to reduce environmental pollution and protect human health.